Development of graphical user interface for economic dispatch problem / Abdul Rahman Abas Azmi - Abas Azmi, Abdul Rahman (2011)
The electric power system is considered the backbone of modern information society. Many other infrastructures and services including telephone, computing, banking, etc will not be operating properly without safe, reliable and economic supply of electricity. Therefore, the power system infrastructure is considered the most critical one and its operating needs to be assured on a daily basis. Simulation programs like Power Dispatch Simulator are essential for teaching undergraduate students about the basic of power system engineering. Moreover, this paper presents a window-based educational simulator with user-friendly graphical user interface (GUI) for the education of power system engineering for solving economic dispatch (ED) problems. In the developed simulator, users can select the number of generator will be used and set the generators either with limit or without limit and also without the losses..